2018
DOI: 10.1111/mcn.12602
|View full text |Cite
|
Sign up to set email alerts
|

Infant formula feeding practices associated with rapid weight gain: A systematic review

Abstract: Excess or rapid weight gain during the first 2 years of life is associated with an increased risk of later childhood and adult overweight and obesity. When compared with breastfed infants, formula fed infants are more likely to experience excess or rapid weight gain, and this increased risk in formula fed infant populations may be due to a number of different mechanisms. These mechanisms include the nutrient composition of the formula and the way formula is prepared and provided to infants. This systematic lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 57 publications
0
83
1
5
Order By: Relevance
“…Merece destaque o elevado teor proteico das PL compostas por fórmula infantil, por serem geralmente adicionadas de farinhas. 28 Conforme já mencionado, as PL preparadas à base de composto lácteo apresentaram teores de micronutrientes superiores aos do LHM, exceto para cálcio. Os compostos lácteos contêm aditivos alimentares e açúcares, 51% de leite (no mínimo) e outros ingredientes lácteos ou não lácteos; por esses motivos, não são considerados substitutos do leite humano e, consequentemente, não são indicados para crianças menores de três anos.…”
Section: Discussionunclassified
“…Merece destaque o elevado teor proteico das PL compostas por fórmula infantil, por serem geralmente adicionadas de farinhas. 28 Conforme já mencionado, as PL preparadas à base de composto lácteo apresentaram teores de micronutrientes superiores aos do LHM, exceto para cálcio. Os compostos lácteos contêm aditivos alimentares e açúcares, 51% de leite (no mínimo) e outros ingredientes lácteos ou não lácteos; por esses motivos, não são considerados substitutos do leite humano e, consequentemente, não são indicados para crianças menores de três anos.…”
Section: Discussionunclassified
“…Considering this high prevalence of formula feeding it is important that parents who are formula feeding their infants are provided with advice on both correct preparation and best practice formula feeding. This is important as formula feeding is related to adverse health outcomes such as rapid weight gain (RWG; Appleton, Russell, et al, ; Mihrshahi, Battistutta, Magarey, & Daniels, ) and overweight or obesity (Wen, Baur, Rissel, Xu, & Simpson, ). It is not clear what proportion of parents formula feeding follow preparation guidelines correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the relationship between formula feeding and RWG, a recent systematic review found that formula with higher protein content, adding cereals into the formula or providing more frequent or larger feeds than an infant requires, could contribute to an infant experiencing RWG (Appleton, Russell, et al, ). The review also found that unresponsive feeding practices such as putting an infant to bed with a bottle and feeding to a schedule rather than infant demand may also contribute to an infant experiencing RWG (Appleton, Russell, et al, ). Providing information to parents on correct preparation and best practices to implement when feeding with formula may reduce the risk of these negative health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is indispensable that pediatricians carefully revise their recommendations about complementary feeding and diet in the first 36 months of life. In particular, beyond sugar overconsumption [5], the excessive protein intake, especially of lactoproteins, has been identified as a risk factor for the premature development of obesity [6][7][8][9] leading to early adiposity rebound [10,11]. On the other side, a correct protein intake may be protective [12].…”
Section: Introductionmentioning
confidence: 99%